Nonhuman DNA typing : - Coyle, Heather Miller (CRC Press/Taylor & Francis, 2008)
This volume covers aspects of nonhuman DNA typing in 11 chapters that cover that basic science, the use of nonhuman DNA evidence in crime solving, collection and preservation, techniques, and analysis. Coyle (forensic science, U. of New Haven) compiles other chapters that describe cat, dog, and insect DNA analysis, use of typing in wildlife investigations, DNA testing methods, forensic fungi, soil typing, and DNA profiling. Chapter authors work in forensic science, genetics, and other sciences and are based around the world.